Evaluating GDF-15 As A Marker of Atherosclerotic Severity Using TIMI Score Stratification in Non-ST Segment Elevation Acute Coronary Syndrome - Namrata, Shah; Mamta, Singh; Pradeep, Agarwal; Shakuntala, Saini; Dinesh, Gautam (Journal of Neonatal Surgery, 2025)
Background: GDF-15, a cytokine of the TGF-β superfamily, is expressed in atherosclerotic plaque macrophages. While several biomarkers have been widely studied in Acute coronary syndrome (ACS), data linking GDF-15 to angiographic severity in non-ST segment elevation acute coronary syndrome (NSTE-ACS), as measured by TIMI score, remain limited. This study investigates the association between GDF-15 levels, atherosclerotic burden, and clinical outcomes in NSTE-ACS patients to enhance risk stratification and guide management. Methods: The study included 100 diagnosed cases of NSTE-ACS, including 34 patients with Non-ST-Elevation Myocardial Infarction (NSTEMI) and 66 with Unstable Angina (UA). Patients were stratified into three risk groups based on the TIMI risk score: low (0–2), intermediate (3–4), and high (≥5). Blood samples were collected at admission, and serum GDF-15 levels were measured using enzyme-linked immunosorbent assay (ELISA). Results: Of the 100 NSTE-ACS patients, 46% were classified as low risk, 39% as intermediate risk, and 15% as high risk based on TIMI scores. High-risk status was more common among males and UA patients. A significant association was found between diagnosis and risk categories (P = 0.014). GDF-15 levels significantly increased across risk groups, with the highest levels in the high-risk group (P < 0.001). The ROC curve analysis showed excellent predictive value for GDF-15, with an AUC of 0.985 (p < 0.001). An optimal cut-off value of >954 pg/mL demonstrated 100% sensitivity and 92.94% specificity in identifying high cardiovascular risk. Conclusion: GDF-15 levels strongly correlate with TIMI risk scores in NSTE-ACS, supporting its role as a promising biomarker for risk assessment and disease severity stratification.